Note on Generalized Distance Matrix of Graphs: Abdul Hameed, Zia Ullah Khan - Team, Support (Thai Journal of Mathematics, 2022)
For any connected graph G with α [0,1], the generalized distance matrix D_α(G) is defined as, D_α(G)= α T(G)+(1 - α)D(G), where T(G) represents a transmission diagonal matrix of G and D(G) is the distance matrix of G. The maximum eigenvalue of generalized distance matrix is called D_α(G) spectral radius. In this paper, we give some new results on generalized distance spectra of complete multipartite graphs. Later in the paper are given some sharp bounds for generalized distance spectral radius of connected graphs.